Non-symmetric Mach-Zehnder interferometer wavelength filter - Kok, Swee Leong; Shaari, Sahbudin (2004)
A non-symmetrical Mach-Zehnder configuration with corrugated waveguide at one of its arm which acts as an interferometer is presented. The interference output intensity of the input light power depends on the operating wavelength, hence acting as a wavelength filter. The function of this wavelength filter is demonstrated by beam propagation method within range from 1000nm to 1800nm.